PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMK DI RAYON 2 KABUPATEN SAMBAS - Santoso, Heri; Chiar, Chiar; Syukri, Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractQuality of education can not be separated from the condition of teachers as one element of education providers. Teachers have positions and roles that are very important and strategic in overall efforts to achieve the quality of education.This research generally aims to reveal the influence of principal leadership and organizational climate on the performance of SMK Rayon 2 teacher Sambas District.Â  Problems in this study as follows: 1) Does the leadership of the principal affect the performance of teachers in SMK Rayon 2 Sambas District? 2) Does the organizational climate affect the performance of teachers in SMK Rayon 2 Sambas District? 3) Does the principal's leadership and organizational climate affect jointly on teacher performance in SMK Rayon 2 Sambas District? The conclusions of this study are as follows: 1) the headmaster's leadership in SMK Rayon 2 Sambas is very good, 2) the organizational climate in SMK Rayon 2 Sambas Regency is good, 3) the performance of SMK Rayon 2 teacher Sambas District is quite good, 4) The headmaster significantly influenced the performance of SMK Rayon 2 teacher Sambas District, 5) the organizational climate significantly influenced the performance of SMK Rayon 2 teacher Sambas district, and 6) leadership of headmaster and organizational climate together significantly influence the performance of SMK Rayon 2 Sambas District. This study suggests that principals should understand the organizational climate because it is seen as the existence of an organization in schools that is formed from the interplay between attitudes and beliefs of parents who are in school and the relationships among individuals in the school to improve the performance of teachers.Â Keywords: Principal Leadership, Organizational Climate, Teacher Performance